Islamic Religious Education in the Era of Afta - Hasbi Indra (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2015)
Abstract Taman Pendidikan Al Qur’an (TPA), Pesantren and Madrasah Diniyah are important parts in the development of Islamic national education. Although the future of those Islamic education is quite difficult to be predicted, they have already become vital components of the national education system. In addition, the quality of this various Islamic institution is also leaded to the International standard education. This article is a qualitative research study which compare and contrast several literatures about Islamic religious education in Indonesia. ASEAN State of Education Report revealed that one of the 2013’s agenda is to develop the quality of education in ASEAN countries. Based on this agenda, Islamic education, which is an important part of the educational system in Indonesia, is also hoped to increase its quality and be ready to compete in International level to face the AFTA. Several efforts have been devoted in order to increase the quality of Islamic religious education. This research is qualitative research study. Abstrak Taman Pendidikan Al Qur’an (TPA), Pesantren dan Madrasah Diniyah merupakan bagian yang penting dalam perkembangan pendidikan Islam nasional. Meskipun cukup sulit untuk diprediksi. masa depan pendidikan Islam tersebut sudah menjadi komponen yang sangat penting bagi sistem pendidikan nasional. Lebih lagi, kualitas institusi Islam yang beragam ini juga mengarah kepada standar pendidikan internasional. Tulisan ini merupakan penelitian kualitatif yang membandingkan dan membedakan beberapa literatur tentang pendidikan Agama Islam di Indonesia. Laporan Bagian Pendidikan ASEAN menunjukkan bahwa salah satu agenda 2013 adalah untuk mengembangkan kualitas pendidikan di negara-negara ASEAN. berdasarkan agenda tersebut, pendidikan Islam, yang merupakan bagian penting darui sistem pendidikan di Indonesia, juga diharapkan dapat meningkatkan kualitasnya dan siap untuk bersaing di tingkat internasional untuk menghadapi AFTA. Beberapa usaha telah dicurahkan untuk meningkatkan kualitas pendidikan agama Islam. How to Cite : Indra, H. (2015). Islamic Religious Education in the Era of Afta.TARBIYA: Journal Of Education In Muslim Society,2(2), 204-221. doi:10.15408/tjems.v2i2.2208. Permalink/DOI:http://dx.doi.org/10.15408/tjems.v2i2.2208